The glucagon like peptide 1 analogue, exendin-4, attenuates oxidative stress-induced retinal cell death in early diabetic rats through promoting Sirt1 and Sirt3 expression. (October 2016) - Zeng, Ying; Yang, Ke; Wang, Fang; Zhou, Liping; Hu, Yong; Tang, Meiling; Zhang, Shijia; Jin, Shuqing; Zhang, Jingfa; Wang, Juan; Li, Weiye; Lu, Lixia; et al.
Abstract: This study was aimed to further investigate the possible mechanisms by which the glucagon like peptide 1 analogue, exendin-4 (EX4), protects rat retinal cells at the early stage of diabetes. EX4 was injected intravitreally into normal and early-stage streptozotocin-diabetic rats. Cell death, reactive oxygen species (ROS), and electroretinogram (ERG) were measured. Sirtuin (Sirt) mRNA and protein were analyzed. In retinas of diabetic rats 1 month after diabetes onset, cell death and ROS level increased significantly, and the b-wave amplitudes and OPs were significantly reduced. Four days after intravitreal EX4 treatment, retinal cell death and ROS level in retinas reduced significantly, and visual function was recovered. In the retinas of early-stage diabetic rats, the expressions of Sirt1 and Sirt3 were also found to be significantly decreased, and both were back to normal levels after intravitreal injection of EX4. In R28 cells, hydrogen peroxide (H2 O2 ) treatment increased ROS and cell death and decreased Sirt1 and Sirt3. With the addition of EX4 into the culture system, the expressions of Sirt1 and Sirt3 were increased, and the H2 O2 -induced ROS and cell death were significantly reduced. These results confirm a mechanism for EX4 to protect retinal cells from diabetic damage and oxidative injury. EX4 reduces retinal cell death and ROS generation by upregulating Sirt1 and Sirt3 expressions in the retina of early-stage diabetic rats as well as in H2 O2 -treated R28 cells. Highlights: EX4 reduces ROS generation and prevents the cell death in diabetic retinas. EX4 improves the visual function of the retinas in diabetic rats. The expressions of Sirt1 and Sirt3 are significantly down-regulated in diabetic retinas. EX4 up-regulates Sirt1 and Sirt3 expression in retinas of diabetic rats. EX4 up-regulates Sirt1 and Sirt3 in H2 O2 -treated R28 cells.